2009
DOI: 10.3945/ajcn.2009.28026
|View full text |Cite
|
Sign up to set email alerts
|

Optimal gestational weight gain ranges for the avoidance of adverse birth weight outcomes: a novel approach

Abstract: Considerably wider optimal GWG ranges than recommended by the Institute of Medicine might be tolerated with respect to avoidance of adverse birth weight outcome. Stratification by maternal body mass index category alone might not be sufficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
99
2
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(109 citation statements)
references
References 29 publications
4
99
2
4
Order By: Relevance
“…Initially, we used the method of analysis introduced in a study by Beyerlein et al [11], to calculate the predicted probability of pregnancy outcomes according to weight gain in primiparous non-smoking women with an average maternal age (overweight, 32.4 years; obese, 32.0 years) and average gestational delivery week (overweight, 38.9 weeks; obese, 38.9 weeks) .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Initially, we used the method of analysis introduced in a study by Beyerlein et al [11], to calculate the predicted probability of pregnancy outcomes according to weight gain in primiparous non-smoking women with an average maternal age (overweight, 32.4 years; obese, 32.0 years) and average gestational delivery week (overweight, 38.9 weeks; obese, 38.9 weeks) .…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the lowest prevalence of poor maternal and neonatal outcomes was observed in women with a weight loss of 0.03 kg/week; therefore, the preferable weight gain is lower than what is currently recommended by the IOM. In a retrospective study on pregnant women in Bavaria, Germany, Beyerlein et al [11] reported that the range of weight gain that does not increase the risk of poor maternal and neonatal outcomes is considerably wide, and that overweight women might benefit from a lower weight gain than that recommended by the IOM, or weight loss in order to deliver infants with a normal birth weight. Although the results of these studies on pregnant women in Western countries were not directly applicable to our study on Japanese pregnant women, the results were consistent with ours.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations